Efektivitas Teori Belajar Gestalt Pada Pendidikan Anak Usia Dini - Riza Mi'rotul Rohmah; Rohmatul Azizah; Risyaf Nabiel Mardiansyah; Arbaiyah Yusuf (Peneliti.net, 2023)
Learning is one of the processes of an education, learning is expected to provide results such as the formation of the character of students, changing attitudes, and creating creative students. Education or learning must start from early childhood, because they have not been affected by bad things. And to create these learning outcomes, comprehensive learning is needed, meaning that studying a symptom is seen as a whole or in totality as contained in Gestalt theory. Gestalt theory is a theory which states that a person will view an object as a whole. Integrated learning is a clear example of the application of Gestalt theory in education